2010
DOI: 10.1371/journal.pgen.1001183
|View full text |Cite|
|
Sign up to set email alerts
|

Common Genetic Variants and Modification of Penetrance of BRCA2-Associated Breast Cancer

Abstract: The considerable uncertainty regarding cancer risks associated with inherited mutations of BRCA2 is due to unknown factors. To investigate whether common genetic variants modify penetrance for BRCA2 mutation carriers, we undertook a two-staged genome-wide association study in BRCA2 mutation carriers. In stage 1 using the Affymetrix 6.0 platform, 592,163 filtered SNPs genotyped were available on 899 young (<40 years) affected and 804 unaffected carriers of European ancestry. Associations were evaluated using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(75 citation statements)
references
References 42 publications
2
73
0
Order By: Relevance
“…However, in the two CML populations not all individuals homozygous for the inducer allele at the flanking markers of qhir1 showed HIR . 0%, a phenomenon known as incomplete penetrance (e.g., Barret et al 2008;Eldar et al 2009;Gaudet et al 2010), while complete penetrance was observed in 1680-F 2 and 1680-F 3 . Yet, genotypes at the actual QTL position are unknown and denser marker coverage would be necessary to more conclusively infer about penetrance.…”
Section: Agreement Between Conceptual Genetic Framework and Qtl Resultsmentioning
confidence: 99%
“…However, in the two CML populations not all individuals homozygous for the inducer allele at the flanking markers of qhir1 showed HIR . 0%, a phenomenon known as incomplete penetrance (e.g., Barret et al 2008;Eldar et al 2009;Gaudet et al 2010), while complete penetrance was observed in 1680-F 2 and 1680-F 3 . Yet, genotypes at the actual QTL position are unknown and denser marker coverage would be necessary to more conclusively infer about penetrance.…”
Section: Agreement Between Conceptual Genetic Framework and Qtl Resultsmentioning
confidence: 99%
“…37 This is the first time this gene has been related with MD; however, OTUD7B gene is altered by amplification in the 7.9% of 482 human breast tumours cases analysed in the study of the Cancer Genome Atlas Network. In fact the role of the genetic variation in the ZNF365 gene, other zinc finger protein (365), in MD variability 12 and also in cancer susceptibility [38][39][40] has been previously described. The relation between genetic variants and MD has been studied by different groups finding significant associations with several inter and intragenic SNPs.…”
Section: Epidemiologymentioning
confidence: 99%
“…A QTL is a region of the genome containing an allelic difference that causes a change in phenotype. Many medically and agriculturally important traits exhibit complex genetic architecture, including phenotypes ranging from diabetes and cancer penetrance to meat quality and frost tolerance in crops (Glazier et al 2002;Heuven et al 2009;Dumont et al 2009;Gaudet et al 2010). QTL with relatively large effects are the easiest to identify and analyze, yet most QTL have small average effects on complex traits (Mackay 2001).…”
mentioning
confidence: 99%